THE EFFECT OF MOTIVATION ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE AT THE FOOD SECURITY AND AGRICULTURE SERVICE OF BINJAI CITY - Ralasen Ginting; Muhammad Isa Indrawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine and analyze the effect of motivation on employee performance with work discipline as an intervening variable. This research was conducted at the Office of Food Security and Agriculture in Binjai City with a population of 80 employees. Sampling was carried out using saturated samples. The research model used path analysis to calculate research using Smart PLS. The results of this study are as follows. Work discipline has a positive and significant effect on employee performance. Motivation has a positive and significant effect on work discipline. Motivation has a positive and significant effect on Employee Performance. Motivation has a positive and significant effect on Employee Performance through Work Discipline.